The Relationship of Interdialytic Weight Gain is Associated with Intradialysis Hypertension in Hemodialysis Patients - Afitiani Maghfiroh; Lina Berliana Togatorop (GLOBAL HEALTH SCIENCE GROUP, 2024)
One of the complications in the hemodialysis process is intradialysis hypertension. Hemodialysis patients also often experience increased interdialytic weight gain (IDWG). IDWG and intradialysis hypertension are each associated with patient mortality and morbidity. This study was conducted to determine the relationship between interdialytic weight gain and intradialysis hypertension in hemodialysis patients at Depok City Hospital. This research method is quantitative with cross sectional design. A total of 92 hemodialysis patients who met the inclusion criteria were selected using purposive sampling technique. Data were collected using a respondent characteristics questionnaire, IDWG scoring sheet, and intradialysis systolic blood pressure observation sheet. The results showed that 37% of respondents were 55-64 years old; 53.3% were female; 48.9% had a high school education; 76.1% of respondents did not work; 75% of respondents had an economic status of <Rp4,878,612.00 (below Depok's minimum wage); 44.6% were of Betawi ethnicity; 80.4% had a history of hypertension; 52.2% had undergone hemodialysis for 6-12 months; 54.3% had ≥2 comorbidities; 59.8% took ≥2 anti-hypertensive drugs; and 81.5% had a fluid intake of ≥500 ml per day. Based on Spearman correlation test, there was a relationship between interdialytic weight gain and intradialysis hypertension in hemodialysis patients at Depok City Hospital (p = 0.014; r = 0.255). Monitoring IDWG and the incidence of intradialysis hypertension is important to pay attention to so that its impact can be prevented, so that the mortality and morbidity rates of patients do not increase in the future.